EFFECT OF DIFFERENT SOURCES OF HORIZONTAL TRANSMISSION OF BACTERIAL FLACHERIE ON ET50 FOR SYMPTOM EXPRESSION AND MORTALITY OF PM X CSR2 - B. L .KAVYASHREE,; , R. N. BHASKAR,; C.DORESWAMY, (The Bioscan, 2020)
Flacherie disease of silkworm Bombyx mori L. is also called as Thatte disease (Thatte roga), Benkiroga (Dhadevu roga) and it was first observed from a village in Malavalli taluk of Mandya district during summer months of 1990 (Doreswamy et al., 2001) cause flaccidity in larva, during which they become feeble, lethargic, vomit gut juice and extrude soft faeces with higher water content. Administration of 10 -5 and 10 -7 dilutions of horizontal sources of inoculum to fourth and fifth instar larvae exhibited significant results. It is very clearly indicated that, decreased bacterial dilution exhibited minimum ET 50 value for symptom expression observed for contaminated faecal pellet (9.01. 9.18; 7.01, 7.35 days) for fourth and fifth instar at 10 -5 and 10 -7 , respectively followed by contaminated bed (9.09, 9.38; 7.18, 7.30 days) and (10.17, 10.25; 8.12, 8.30 days). The trend was found same in ET 50 for larval mortality (9.97, 10.12; 8.01, 8.13 days). It was also concluded that, the horizontal transmission was found minimum in contaminated rearing equipment (9.42, 9.72; 11.03, 11.65 days) and (7.51, 7.67; 9.07 9.72 days) used for rearing compared to other sources of horizontal transmission. Which inturn recorded maximum number of days to express the disease in both the instars of PM x CSR2.